2001
DOI: 10.1016/s0735-1097(01)01463-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of left atrial chamber and appendage thrombi in patients with atrial flutter and its clinical significance

Abstract: The findings of a low prevalence of LA appendage thrombi (1%) in patients with AFl and a close correlation between a history of previous embolism and paroxysmal AF support the current guidelines that patients with pure AFl do not require anticoagulation therapy, whereas patients with AFl and paroxysmal AF should receive anticoagulation therapy. In addition, the presence of clinical risk factors should alert the physician to an increased likelihood for a thrombogenic milieu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 34 publications
3
39
3
1
Order By: Relevance
“…Our study does confirm previous reports where pAFl patients undergoing CV have a low prevalence of AT (3% in our population) while AFl patients with previous AF history had a much higher prevalence of AT (32%) [3][4][5][6][7].…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Our study does confirm previous reports where pAFl patients undergoing CV have a low prevalence of AT (3% in our population) while AFl patients with previous AF history had a much higher prevalence of AT (32%) [3][4][5][6][7].…”
supporting
confidence: 91%
“…Prevalence of AT and LASEC during atrial flutter (AFl) is debated, previous studies report very different results, ranging from 0% to 21% [3][4][5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas some studies suggest that the stroke risk with atrial flutter (an organized, macroreentrant arrhythmia) is similar to that of AF, 13,14 others suggest a continuum of stroke risk that increases with greater atrial rate and disorganization. 15,16 The putative mechanisms of thromboembolism in AF include development of mechanical dysfunction and a proinflammatory and procoagulant state, with resultant thrombus formation in the complex, pectinate-rich structure of the left atrial appendage (LAA) (Figure 1), [17][18][19] although the possibility that AF is merely a marker for the presence of stroke risk factors exists. Moreover, the LAA demonstrates great interindividual morphological heterogeneity.…”
Section: The Spectrum Of Atrial Tachyarrhythmias and Stroke Risksmentioning
confidence: 99%
“…2,3 This decreases the chance of developing a thrombus by preventing blood stasis in the atrial chambers. 2,[5][6][7][8][9]11 In previous trials, some clinical and echocardiographic predictors for thromboembolism were defined in patients with atrial fibrillation. Several studies evaluating the thromboembolic risk in these patients reported that the prevalence of atrial thrombi is 0-11% 5-10 and the prevalence of spontaneous echo contrast is 6-42%.…”
Section: Introductionmentioning
confidence: 99%